Comparative investigation of the static and dynamic properties of CO2 foam and N2 foam. (23rd May 2016) - Lv, Mingming; Wang, Shuzhong; Zhai, Zhende; Luo, Xiangrong; Jing, Zefeng
Abstract: Foam flood using CO2 can both enhance oil recovery and achieve geological storage of CO2, which has attracted increasing attention in the last two decades. This work systematically investigates the behaviours of CO2 and N2 foams both in bulk and porous media by static foam tests and core flood experiments. The stability and foamability of CO2 and N2 foams were compared in static foam tests. The foam texture showed that CO2 foam bubbles were relatively larger and exhibited a wider size distribution than N2 foam bubbles, which was detrimental to foam stability. Furthermore, steady‐state foam flows of CO2 and N2 foams at a fixed liquid flow rates were comparatively investigated with a foam quality range of 30–98 %. The difference between CO2 foam stability and N2 foam stability in porous media was relatively smaller, compared with the difference in bulk. Additionally, the analysis of foam rheology showed that foam exhibited different non‐Newtonian flow characteristics at different foam qualities, and the resistance to shearing of CO2 foam was lower than that of N2 foam. Finally, the results of foam flood experiments demonstrated that the oil recoveries of CO2 foam were lower than those of N2 foam with a co‐injection strategy under both subcritical and supercritical conditions. Compared with results in the atmosphere environment, the oil recovery of CO2 foam flood was higher under supercritical conditions.